The societal impact of meaningful social interactions during online focus groups - Connor Smith (Societal Impacts)
Against a backdrop of increasing levels of discontent and division reported in democratic societies, meaningful social interactions (especially between strangers) are clearly important to study. Drawing on observations during previous research projects, this article explores whether and how online focus groups (OFGs) can be leveraged to facilitate meaningful social interactions between unfamiliar interaction partners, and the extent to which these interactions have the potential to create societal impact. Our findings suggest that OFGs can facilitate a combination of “emotional”, “informational”, and “tangible” impacts for participants, helping to make social interactions meaningful. Meanwhile, these “individual impacts” could translate to “societal impacts” by empowering people to better participate (and participate better) in the public sphere. This outcome could be accelerated if individuals share newly acquired knowledge onwards with their community, generating a positive feedback loop of further meaningful social interactions. Our findings imply that researchers should strive to ensure that qualitative social research delivers direct value to the participants who take part, separate from the potential (thematic) value it has for the academic(s) involved. This ambition could be supported by academic funding frameworks that recognize “direct value for participants” as a desirable (and assessed) criterion.